INTEGRATED TICKETING SYSTEM OF PUBLIC TRANSPORT IN JAKARTA VS VÄRMLAND, SWEDEN - Teguh Himawan Ronggosusanto (Journal of the Civil Engineering Forum, 2013)
The heightened mobility of people in the DKI Jakarta province and surrounding area requires balance of the development public transport services. One of service attributes in public transportation is ticketing system. Currently, the ticketing system in Jakarta needs to be improved and still not integrated. Therefore, the importance to develop and implement a new integrated ticketing system to increase the competitiveness and attractiveness of public transports. It also gives an opportunity to the operators in order to implement several of ticket prices. There are some of barriers that faced by operators in development a new integrated ticketing system such as; institutional issue, resources integration, and financial problems. In order to describe and analyze the development of a new integrated ticketing system, this thesis uses a qualitative research approach and five sources of evidence i.e. documentation, archival records, an interview, direct and participant observations through a survey using the form of questionnaires that distributed to the public transport users. Further, this study also uses the case of Värmlandstrafik AB as the comparative study and the theoretical basis of the new services development as an approach to assess the possibility of implement a new integrated ticketing system. It aims to investigate the ticketing system phenomenon using information and data observations as materials to analyze, explore, and provide depth explanation. By analyzing data from a survey of passengers, this study gave a description and explanation related the characteristic and the travel behavior of passenger, also an assessment of ticketing system that underlies the development a new integrated ticketing system. Then, using the comparative case study of Värmlandstrafik AB that already implement an integrated ticketing system and the self-services in provision of public transport services gave an analysis what needs to prepare for implement a new integrated ticketing system consider to the organizational process.